PERLINDUNGAN HUKUM TERHADAP NASABAH KORBAN KEJAHATAN PENGGANDAAN KARTU ATM PADA BANK SWASTA NASIONAL DI DENPASAR - Komang Juniawan (Jurnal Magister Hukum Udayana (Udayana Master Law Journal), 2013)
Responsibility of the bank to refund customers money that became victims of ATMcard duplication is the bank have responsibility to refund the customer money, so that theloss of customer funds was caused by his own negligence, then the bank is not haveresponsibility to refund losses suffered by customers. Legal efforts taken by the bank torefund customers money that became victims of ATM card duplication such as :Clarification of customer complaints by checking the data to determine the customer'saccount transactions that cause a reduction in the customer's account balance, thendeliver customer transactions was conducted customer; Checking customer transactionsallegedly clumsy, one of which is checking the CCTV at the cash machine withdrawalsare not recognized by the customer, checking and known whether the transaction isconcluded that the transaction is correct or odd transactions; Returns missing customerfunds, if it is concluded that the clients do not make transactions recorded in thecustomer's account, and making a crime report in the ATM card duplication police to dothe investigation against the perpetrators